The effect of pyridine modification of Ni-DOBDC on CO2 capture under humid conditions - Bae, Y.; Liu, Jian; Wilmer, C.; Sun, H.; Dickey, A.; Kim, M.; Benin, A.; Willis, R.; Barpaga, D.; LeVan, M.; Snurr, R. (The Royal Society of Chemistry, 2014)
The metal-organic framework Ni-DOBDC was modified with pyridine molecules to make the normally hydrophilic internal surface more hydrophobic. Experiments and molecular simulations show that the pyridine modification reduces H 2O adsorption while retaining substantial CO2 capacity under the conditions of interest for carbon capture from flue gas. © The Royal Society of Chemistry 2014.